Cytogenetic alterations in multiple myeloma: prognostic significance and the choice of frontline therapy - Stella, Flavia (2015)
Multiple myeloma tumor cells demonstrate multiple and often complex genetic lesions as evaluated by standard cytogenetic/FISH studies. Over the past decade, specific abnormalities have been associated with standard or high-risk clinical behavior and they have become strong prognostic indicators. Further, as evidenced by recent randomized clinical trials, the choice of front-line therapy (transplant vs. no transplant, inclusion of novel drugs such as bortezomib, thalidomide, and lenalidomide) may be able to overcome the adverse effect of high-risk genetic lesions.